Pengaruh Aset Berwujud, Pertumbuhan Penjualan dan Risiko Bisnis terhadap Struktur Modal - Sari, Ayu Permata; Nurbaiti, Beti; Ningrum, Endah Prawesti; Nuryati, Tutty; Yulaeli, Tri (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
The property and real estate sector has faced significant challenges in recent years, particularly due to the Covid-19 pandemic and rising interest rates. These conditions have impacted corporate financing decisions, especially capital structure. This study aims to examine the effect of tangible assets, sales growth, and business risk on capital structure among property and real estate companies listed on the Indonesia Stock Exchange. A quantitative approach was used, employing secondary data derived from annual financial reports for the period 2019–2023. To meet the classical assumption requirements and enhance data normality, capital structure data was transformed using a square root, and the data series was differenced, resulting in a final sample of 176 firm-year observations from 44 companies selected via purposive sampling. Data were analyzed using panel data regression with the common effect model, supported by classical assumption tests. The findings reveal that business risk has a significant negative effect on capital structure, while tangible assets and sales growth have no significant influence. Simultaneously, the three independent variables significantly affect capital structure. These results imply that firms with high business risk tend to be more cautious in utilizing debt, aligning with the trade-off theory. Conversely, tangible assets and sales growth do not necessarily determine capital structure decisions in the observed sector.